Rancang Bangun Pencuci Tangan Berbasis Water Level Control di Pesantren Darul Muttaqin Kabupaten Sinjai - Rani Bastari Alkam; Suriati Abd. Muin (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Washing hands using soap is one of the three main movements of an effective health protocol to mitigate the transmission of Covid-19 and other infectious diseases. To apply this protocol, Darul Muttaqin Islamic Boarding School as a partner of this activity lacks of physical infrastructure to support and encourage the habit of washing hands in the community. This program is directed at procuring hand washing equipment with a water level control and an integrated disposal system at the site. The form and stages of the program are formulated based on intensive discussions with the partners. The hand washing equipment has been produced in the design and the manufacturing stage. The design stages include the model design, the dimension determinations, and the budget plan calculation. While the manufacturing stages include the manufacture of the structure, installation of reservoirs and accessories, electrical installations, and installation of drainage and sewer lines. The dual-function hand washing device is an output product of this program which has been handed over to partners to be used as best as possible by the students.